Characteristics and progression‐free survival of Afro‐Caribbean men with metastatic hormone‐sensitive prostate cancer at the time of diagnosis. Issue 14 (28th July 2021) - Rossignol, Thibault; Gourtaud, Gilles; Senechal, Cédric; Sadreux, Yvane; Roux, Virginie; Blanchet, Pascal; Brureau, Laurent
Abstract: Introduction and Objectives: Metastatic hormone‐sensitive prostate cancer (mHSPC) accounts for 12% of prostate cancers diagnosed in Guadeloupe according to the Guadeloupean cancer registry. Most published studies have been conducted on the Caucasian population, whereas data concerning mHSPC in the Afro‐Caribbean population are lacking. We aimed to describe the patient characteristics and estimate the progression‐free survival of men with mHSPC in an Afro‐Caribbean population according to the available treatment. Patients and Methods: This was a monocentric retrospective study that consecutively included 133 men with mHSPC between January 1, 2015 and December 31, 2019 at the University Hospital of Guadeloupe. The primary endpoint was a description of the patients' characteristics with a description of complications at diagnosis. The secondary endpoint was progression‐free survival. Kaplan–Meier survival and Cox proportional hazard analyses were performed. Results: The median age at diagnosis was 71 years. The median prostate‐specific antigen (PSA) was 147 ng/ml and 37% of patients presented with a disease‐related complication at diagnosis. The survival analysis according to treatment showed median survival of 15 months for the androgen deprivation therapy (ADT) + chemotherapy group, 20 months for the ADT + new hormone therapy group, and 21.5 months for the ADT alone group, with no significant difference between the three therapeutic options (log‐rank test: 0.27). In univariate analysis, none of the patient characteristics at diagnosis (i.e., age, PSA, bone lesions, visceral lesions) were significantly associated with the risk of progression, regardless of the treatment. Conclusion: There was no significant difference in terms of progression‐free survival between currently validated treatments administered in the first line, regardless of the tumor volume or risk group. Future studies with larger numbers of patients and involving molecular factors are required to confirm or invalidate these results and understand the evolution of prostate cancer in our population and thus better prevent complications related to the disease.